Moderating Effect of Information Asymmetry on the Signalling Role of IPO Lockup Provision. Issue 4 (August 2019) - Yahya, Norliza Che; Rahim, Ruzita Abdul
Abstract: This article examines the moderating effect of information asymmetry on the relationship between parameters of lockup provision and flipping activity of Malaysian initial public offerings (IPOs). While the main purpose of lockup provision is to promote commitment of major shareholders for the well-being of the IPO issuing companies at least throughout the lockup period, its role could also extend as a signalling device. Information asymmetry is prevalent in the context of IPOs because information on the issuing firms is normally very limited that the evaluation of the firms' true value becomes difficult. This study postulates that the lockup provision has a greater influence on flipping activity in higher information asymmetry companies than in lower ones. Using data from 370 Malaysian IPOs issued from January 2000 to December 2012, the results of the multiple regression analyses show that both lockup ratio and lockup period have significantly negative impacts on flipping activities. Since lockup period is uniformly longer (1 year) prior to the 2008 Equity Guidelines revision, the results imply that investors have a greater tendency to flip during the post-2008 revision period when major shareholders are perceived to be less strongly accounted for their firms' performance. The results also show that information asymmetry moderates the negative relationship between lockup provision and flipping activity, specifically, in regard to lockup period.